“Sabda Bayu” Rajas Tamas Octopus Methapor in Contemporary Painting Work - I Made Bendi Yudha; Anak Agung Gde Alit Geria; I Wayan Gulendra; I Made Jodog (Institut Seni Indonesia Denpasar, 2023)
Gurita in English is called Octopus which often refers only to animals of the genus Octopus. This creation is based on the results of research on the octopus which is used as a symbolic brand icon to reveal the existence of the current social, cultural, economic and political realities. In interpreting the characteristics of the shape and nature of the Octopus, it is expressed through a metaphorical visual language to represent the value of rajas and tamas that permeates the human soul. This study aims to present visual aesthetic values and symbolic meanings through the processing of forms of abstraction, distortion and deformation, as an expression of the growing influence of global capitalism in people's lives which are dominated by the energy of guna rajas and guna tamas. The research method is carried out by observation, interviews, documentation and media reset as well as the stages of creation through exploration, improvisation and formation. The visualization of the work presents the complexity of lines, colors, shapes and textures by carrying out technical and coloring hybridization, in order to present meaningful forms which are symbolic representations of the rajas and tamas that dominate people's lives today. The concept of creation offered is a form of concern for the emergence of moral and moral degradation in society which has implications for the fading of ethical values, and a sense of humanity as contained in animal values which promote love and tolerance among others, which in Hinduism is known as term; mutual sharpening, compassion and care, sagilik, saguluk, salunglung sabayantaka, paras paros sarpanaya.It is not enough for this kind of concept to be offered only through works of art, but it really needs to be communicated in the wider social field, so that interactive and communicative dialogue occurs, while at the same time providing education and enlightenment, so as to create new awareness, so that we have the ability and strength to facing or overcoming current global issues.